FREQUENCY OF HYPERGLYCEMIA IN PATIENTS ON INTRAVENOUS STEROID THERAPY FOR RESPIRATORY ILLNESSES (The Research of Medical Science Review, 2024)
Objective: To determine the frequency of steroid-induced hyperglycemia in patients admitted with respiratory illness. Methods: This cross-sectional study study was conducted in the medicine unit of Shifa International Islamabad from April 2024 to October 2024. All patients admitted to the department of medicine due to some pulmonary illness, such as acute exacerbation of COPD or asthma, who were hospitalized for at least 3 days were included. Frequency of hyperglycemia was determined. Results: In this study, a total of 175 patients were recruited. The mean age of the participants was 52.7 years, with a standard deviation of 8.4 years. When considering the presence of comorbidities, diabetes was found in 65 (37.1%) individuals, and hypertension in 83 (47.4%) patients. Out of 175, hyperglycemia was diagnosed in 73 (41.71%) patients. Conclusion: Hyperglycemia is a common complication in patients receiving corticosteroids admitted with respiratory illness. So blood glucose levels should be routinely monitored in patients receiving steroids, and appropriate management should be done in these patients to maintain blood sugar levels in normal limits.